POLA KONSUMSI MASYARAKAT: STUDI PENGELUARAN KONSUMSI 5 KOMODITAS MAKANAN TERBESAR RUMAH TANGGA PERDESAAN DI SULAWESI TENGAH - Yusuf, Dahlia; Moelyono, Mauled; Ichwan, Mohamad (Katalogis, 2019)
The development in rural areas since support for development funding has the tendency to change the pattern of household consumption, therefore attention to consumption patterns in rural areas has become a good topic for research. This study aims to determine the consumption patterns of the five largest food commodities by utilizing descriptive analysis of 6,178 households obtained from the 2017 Susenas national secondary data. Found 8 types of dominant food commodities in rural household consumption and identified as the 5 largest food commodities, namely: (1) rice; (2) cigarettes; (3) mixed rice; (4) fish; and (5) sugar. It was also found that food consumption tends to increase along with increasing income.